Climate Change and Climate Justice in Rural Sindh: Evidences and Experiences from the Rural-Based Population of Khairpur District - Magsi, Khadim Hussain; Hussain, Nazar; Oad, Sahib; Mirani, Zahid Hussain (Pakistan Journal of Humanities and Social Sciences, 2023)
The present research study was carried out to collect the evidences of the climate change impact on the local communities of district Khairpur and to understand the views of people how they experience the climate change impact on their lives. The current study was undertaken employing the qualitative research methodology with a small sample size of villages aging from 25 to 65 age from a single union council. Qualitative research cannot be generalized as qualitative findings are generalized where large sample size is selected to collect the data. The study was carried out on four major areas of the climate change stressors which are Changes in weather patterns, floods, heat waves and heavy rains. All four stressor have direct severed effect on the lives of rural-based population. The findings of the study reveal that climate change has severe impact on the lives of common people which bear lots of pain in terms of agriculture loss where their standing crops are vanished away , their homes are destroyed completely, livestock is dying off due to the diseases spread and lack of pastures in the vicinity where flooded water stand. Other than this, findings tell us that the role of government seems very pathetic towards the affected people of district Khairpur where score of people have no food items to eat, no shelter to live in and other temporary things at the time of heavy rains and floods. This study can be a torch bearer for the policy makers, governments to formulate the policies according to the ground realities. The vulnerabilities of people due to these climate change stressors are visible to governments. Hence, Climate disasters are affecting every corner of the Sindh, and its marginalized communities are left to face a disproportionate share of the impacts of climate change which is violation of UN Framework for climate change.